2009
DOI: 10.1111/j.1651-2227.2008.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 and transforming growth factor‐β1 in cord blood: relationship with paternal allergy and cesarean section

Abstract: Paternal allergy and cesarean section are associated to decreased TGF-beta1, which might be the mediator of the increased risk of atopy development. Cord blood IL-10 and TGF-beta1 levels of our newborn series could be used as reference values for further studies on these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(33 reference statements)
0
4
1
Order By: Relevance
“…However, TGFb1 levels of cord blood were not consistent and very different in the past reports [6][7][8][9]. To our knowledge, there has been no previous report of identification of a relationship between the serum level of TGFb in cord blood and the prevalence of neonatal complications.…”
Section: Introductioncontrasting
confidence: 66%
See 1 more Smart Citation
“…However, TGFb1 levels of cord blood were not consistent and very different in the past reports [6][7][8][9]. To our knowledge, there has been no previous report of identification of a relationship between the serum level of TGFb in cord blood and the prevalence of neonatal complications.…”
Section: Introductioncontrasting
confidence: 66%
“…Briana et al reported that the 50th percentile of TGFb1 was around 5000 pg/ml in both appropriate for gestational age and intrauterine growth restriction infants [7]. Balossini et al reported an interquartile range of 29,500-55,100 pg/ml of TGFb1 in cord blood [8], and Hrd et al reported an interquartile range of 24,512 and 103,040 pg/ml of TGFb in cord blood from newborns of healthy mothers [9]. The variety of these results might be influenced by the method used to measure the serum level of TGFb.…”
Section: Constitutively Extremely High Level Of Tgfb1 and Tgfb2 Exprementioning
confidence: 96%
“…In a genome wide scan of ADHD subjects [34], 2 SNPs were associated with the inattentive phenotype. While IL-16 levels did not differ between the groups studied, they correlated positively and IL-10 levels correlated negatively with the experience of allergy across all subjects: (see [91] on low IL-10 transmission reflecting paternal allergy). Exactly paralleling this were similar correlations with S100B.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean section was associated with reduced pro-inflammatory cytokine responses to TLR1/2 stimulation, followed by an increased abundance of bacterial colonization in the airway during late infancy, therefore increasing the risk of infantile wheezing (48). Levels of transforming growth factor (TGF)-β1 were lower in newborns following cesarean section (49). Hence, newborns born through vaginal delivery and exposed to higher levels of TGF-β1 may exhibit more protection toward atopy at later life, potentially reflecting the capacities of TGF-β1 to skew the production of IgE toward non-inflammatory isotypes IgG4 and IgA (50).…”
Section: Maternal Protective Influences Over Offspring Allergymentioning
confidence: 99%